2021
DOI: 10.1021/acs.langmuir.1c02187
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity of Self-Assembled Monolayers of Alkanes: Fluorination, Density, Roughness, and Lennard-Jones Cutoffs

Abstract: The interplay of fluorination and structure of alkane self-assembled monolayers and how these affect hydrophobicity are explored via molecular dynamics simulations, contact angle goniometry, and surface-enhanced infrared absorption spectroscopy. Wetting coefficients are found to grow linearly in the monolayer density for both alkane and perfluoroalkane monolayers. The larger contact angles of monolayers of perfluorinated alkanes are shown to be primarily caused by their larger molecular volume, which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…Recently, there have been theories developed to predict the transitions from hydration repulsion to adhesion based on the contact angles of asymmetric hydrophilic and hydrophobic surfaces. Whether these theories (originally developed for the partially charged polar surfaces) may be extended to the surfaces with high charge densities such as the calcites explored in this work remains an open question and is very interesting for future study.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been theories developed to predict the transitions from hydration repulsion to adhesion based on the contact angles of asymmetric hydrophilic and hydrophobic surfaces. Whether these theories (originally developed for the partially charged polar surfaces) may be extended to the surfaces with high charge densities such as the calcites explored in this work remains an open question and is very interesting for future study.…”
Section: Resultsmentioning
confidence: 99%
“…Only in several control systems full long-range Coulomb interactions were realized via the PPPM method with a precision of 10 –6 instead of using eq 3 . 43 Regarding the treatment of L-J interactions, it has been demonstrated that the contact angle, that is, the work of solid–liquid adhesion, is also sensitive to the L-J cutoff length, 44 where best agreement with experimental measurements was achieved by treating the L-J dispersive term as long-range, equivalent to that of Coulomb. Indeed, many force fields tend to underestimate surface tensions, and considering long-range dispersion forces often brings those values closer to the experimental ones, 45 which creates a predicament as most force fields were optimized under an assumption of short-range L-J interactions.…”
Section: Simulation and Analysis Methodsmentioning
confidence: 99%
“…As opposed to the excellent agreement of our WCA predictions with experimental data using a finite LJ cut-off of 12.0 Å, recent work by Carlson et al has demonstrated the importance of considering long-range LJ interactions to accurately determine the interfacial properties of surfaces. 71 Therefore, to understand whether the LJ cut-off impacts the hBN surface's wettability, we fixed the electrostatic interaction cut-off at 12.0 and 24.0 Å for pristine hBN and hBN with exposed edges (0.058 nm/nm 2 ), respectively, and varied the LJ cut-off from 12.0 to 30.0 Å, while determining the work of adhesion. The corresponding work of adhesion values for bulk hBN and hBN with exposed edges are tabulated in the Supporting Information, Section S5.…”
Section: Effect Of Interfacial Electrostatic Interactions On the Work...mentioning
confidence: 99%